1996
DOI: 10.1002/etc.5620151123
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of butyltin accumulation and its biomagnification in steller sea lion (Eumetopias jubatus)

Abstract: The present study was conducted to examine sex difference, age, and temporal trends of butyltin accumulation and its biomagnification in Steller sea lion (Eumetopias jubatus) collected from Alaska, USA, during 1976-1985 and from Hokkaido, Japan, during 1994 Average concentration of total butyltin compounds (⌺BTs) in the liver of Steller sea lion from Alaska (19 ng/g wet weight) was much lower than those from western and eastern Hokkaido, Japan (150 and 220 ng/g), respectively. This result suggests that Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…However, the high coefficient of variation of the data (CV = 95% for liver, n = 8; and 91% for kidney, n = 7) did not enable any significant difference in the residue pattern of BT Appl. Although the number of samples was too small to discern any sex-related variations, this result appears to be in line with previous studies on Risso's dolphin, 24 the Steller sea lion 17 and harbour porpoise. Chem.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, the high coefficient of variation of the data (CV = 95% for liver, n = 8; and 91% for kidney, n = 7) did not enable any significant difference in the residue pattern of BT Appl. Although the number of samples was too small to discern any sex-related variations, this result appears to be in line with previous studies on Risso's dolphin, 24 the Steller sea lion 17 and harbour porpoise. Chem.…”
Section: Resultssupporting
confidence: 91%
“…16 Various studies have shown that TBT accumulates in aquatic organisms, mainly those at lower trophic levels in the food web (e.g. 24,25 These studies have shown that TBT accumulates and is biomagnified by marine mammals, irrespective of sex; accumulation is generally greater in early life and the liver appears to be the organ where the highest concentrations are found. Many recent studies have focused on tissue concentrations and distribution of TBT and its metabolites in marine mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, furbearing animals such as river otters may eliminate butyltin compounds during their annual molting cycle since butyltins have a tendency to bind to structural proteins in fur and hair. Elimination of butyltin compounds by molting has been reported in Stellar sea lion, a fur-bearing marine mammal (Kim et al 1996b). In any case, our results suggest the accumulation of butyltin compounds in river otters from inland rivers.…”
Section: Resultsmentioning
confidence: 99%
“…For a complete assessment of the impact of butyltin compounds in aquatic ecosystems, it is necessary to examine the accumulation and effects of these compounds in various organisms in the food chain. Our recent studies have shown that butyltin compounds accumulate in body tissues of marine mammals and water birds at significant concentrations, and that butyltin contamination in higher trophic level animals in the food chain is widespread (Iwata et al 1995;Kannan et al 1996Kannan et al , 1997aKannan et al , 1998Kannan and Falandysz 1997;Kim et al 1996aKim et al , 1996bGuruge et al 1996;Tanabe et al 1998).…”
mentioning
confidence: 99%
“…Marine gastropods and oysters are among the most susceptible organisms, but fish are affected as well, although at concentrations of 1-10 g/L. However, the long-term ecotoxicological effects of organotins on the structure and function of aquatic ecosystems are still not well understood, particularly with respect to biomagnification in food webs (Guruge et al, 1996;Jak et al, 1998;Kannan et al, 1996;Kim et al, 1996;Stäb et al, 1996).…”
Section: Ecotoxicitymentioning
confidence: 99%